Pengaruh Label Halal Kualitas Produk dan Harga terhadap Keputusan Pembelian Produk Skincare pada Konsumen Muslim di Kota Jambi - Suci Bunga Mentari.Z; Rofiqoh Ferawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of halal labels, product quality, and price on purchasing decisions for skincare products among Muslim consumers in Jambi City. A quantitative method was employed using a questionnaire distributed to 100 respondents, and the data were analyzed with SPSS. The results indicate that halal labels have a significant effect on purchasing decisions, as evidenced by a significance value of 0.001 < 0.05. Similarly, product quality and price also show significant effects with a significance value of 0.001 < 0.05. Simultaneously, halal labels, product quality, and price significantly influence purchasing decisions, contributing 82% to the variation in consumer choices. These findings highlight that the three variables collectively serve as key determinants shaping Muslim consumers’ decisions when selecting skincare products.